INVESTASI MENURUT PERSPEKTIF EKONOMI ISLAM - Hayati, Mardhiyah (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract-Investment is needed by a person to add to the source of its income in order to cover the necessities of life is very urgent that can not be fulfilled from daily earnings , in addition, there are reasons for someone to invest among others to profit as much as possible , future security, protect profits , earn passive income, realizing the desire to achieve the goal hereafter.Someone who would invest let the terms and conditions that are prohibited and which are allowed to invest in making it useful for her to the world and the hereafter, as contained in the Koran, hadith, Consensus and qiyas. Islam strongly encourages people to invest, it is motivated by the doctrinal foundation of the order to pay Zakat for people who have assets that are not productive (idle assets), otherwise productively managed assets are not subject to the obligation of zakat. The new Zakat shall be levied on the results that have been obtained through these investments.